Distribution and potential risk factors of bisphenol a in serum and urine among Chinese from 2004 to 2019 - Zhang, Wenjing; Li, Yanting; Wang, Tao; Zhang, Xinglin; Zhang, Jianzhong; Ji, Xiaoya; Lu, Lin (Frontiers in Public Health, 2024)
Background: Bisphenol A (BPA) is an oil-derived, large-market volume chemical with endocrine disrupting properties and reproductive toxicity. Moreover, BPA is frequently used in food contact materials, has been extensively researched recently, and widespread exposure in the general population has been reported worldwide. However, national information on BPA levels in general Chinese people is lacking.Methods: This study collected and analyzed 145 (104 in urine and 41 in serum) research articles published between 2004 and 2021 to reflect the BPA internal exposure levels in Chinese populations.The Monte Carlo simulation method is employed to analyze and estimate the data in order to rectify the deviation caused by a skewed distribution.Results: Data on BPA concentrations in urine and serum were collected from 2006 to 2019 and 2004 to 2019, respectively. Urinary BPA concentrations did not vary significantly until 2017, with the highest concentration occurring from 2018 to 2019 (2.90 ng/mL). The serum BPA concentration decreased to the nadir of 1.07 ng/mL in 2011 and gradually increased to 2.54 ng/mL. Nationally, 18 provinces were studied, with Guangdong (3.50 ng/mL), Zhejiang (2.57 ng/mL), and Fujian (2.15 ng/mL) having the highest urine BPA levels. Serum BPA was investigated in 15 provinces; Jiangsu (9.14 ng/mL) and Shandong (5.80 ng/mL) were relatively high. The results also indicated that males' urine and serum BPA levels were higher than females, while the BPA levels in children were also higher than in adults (p <0.001). Furthermore, the volume of garbage disposal (r = 0.39, p < 0.05), household sewage (r = 0.34, p < 0.05), and waste incineration content (r = 0.35, p < 0.05) exhibited a strong positive connection with urine BPA levels in Chinese individuals.Despite using a data consolidation approach, our study found that the Chinese population was exposed to significant amounts of BPA, and males having a higher level than females.Besides, the levels of BPA exposure are influenced by the volume of garbage disposal, household sewage, and waste incineration content.